Bryophytes as a model for the study of ecophysiological adaptation to environmental conditions (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
It was established 11 typical features of adaptive strategy of the bryophytes as descendants of the first embryophytes, which represent gametophytic direction of the higher plants’ evolution. Each of the feature of strategy is briefly described and noted different from the vascular plants biological, morphological, physiological and genetic characteristics of adaptation. It was shown that poikilohydry and desiccation tolerance are one of the determinative features of ecophysiological adaptation of bryophytes.
Keywords: bryophytes, gametophyte, ecophysiological adaptation, poikilohydry, desiccation tolerance.